Epidural Spinal Electrogram Provides Direct Spinal Recordings in Awake Human Participants - Burke, John F.; Kunwar, Nikhita; Yaroshinsky, Maria S.; Louie, Kenneth H.; Shirvalkar, Prasad; Su, Paul; Henry, Melanie; Pasvankas, George; Poree, Lawrence; Jacques, Lines; Wang, Doris D. (Frontiers in Human Neuroscience, 2021)
Little is known about electrophysiological activity of the spinal cord in voluntary movement control in humans. We present a novel method for recording electrophysiological activity from the human spinal cord using implanted epidural electrodes during naturalistic movements including overground walking. Spinal electrograms (SEGs) were recorded from epidural electrodes implanted as part of a test trial for patients with chronic pain undergoing evaluation for spinal cord stimulation. Externalized ends of the epidural leads were connected to an external amplifier to capture SEGs. Electromyographic and accelerometry data from the upper and lower extremities were collected using wireless sensors and synchronized to the SEG data. Patients were instructed to perform various arm and leg movements while SEG and kinematic data were collected. This study proves the safety and feasibility of performing epidural spinal recordings from human subjects performing movement tasks.